ALLERGIC RHINITICAL THERAPY WITH ACUPUNCTURE, LEGUNDI AND TEMULAWAK HERBS - Septriana, Maya; Purnamasari, Novita; Studiawan, Herra (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Allergic rhinitis is an inflammatory disease of the nasal mucosa mediated by IgE (immunoglobulin E) with the main mediator histamine. Rhinitis in the science of Traditional Chinese Medicine (TCM) is called Bi Yuan (influenza) and Bi Zhi (nasal congestion). Cases of allergic rhinitis experienced by patients are complaints of repeated sneezing up to 10 times in the morning with rhinorrhea (runny nose). Patients classified as allergic rhinitis with differentiation of hot moist syndrome with splenic deficiency. Purpose: To prove the effect of acupuncture combination therapy on Yintang point (EXHN 3), Yinxiang (LI 20), Zusanli (ST 36), Taibai (SP 3) with herbal legundi (Vitex trifolia) and temulawak (Curcuma xanthorrhiza) in patients with allergic rhinitis. Method: Handling allergic rhinitis with acupuncture and herbal therapy methods. Acupuncture therapy was carried out at Yintang point (EXHN 3), Yinxiang (LI 20), Zusanli (ST 36), Taibai (SP 3) with the principle of eliminating hot humidification and toning of the spleen. In herbal therapy, patients are given herbal legundi (Vitex trifolia) and ginger (Curcuma xanthorrhiza). Result: The active compounds viteosin-A, viteksikarpin, and vitetrifolin-E which can inhibit releasing histamine and curcumin as anti-inflammatory have an effect on sneezing in allergic rhinitis. In handling allergic rhinitis, acupuncture therapy given 12 times, once every two days. Herbal therapy given for 14 times, taken every 2 days interval, 3 times a day with a dose of 5.2 grams of legundi and 4.2 grams of ginger. This therapy overcome the symptoms of sneezing and rhinorrhea in allergic rhinitis. Conclusion: Acupuncture and herbal therapy can be used to overcome sneezing and rhinorrhea in allergic rhinitis.